Predictors of Army National Guard and Reserve Members' Use of Veteran Health Administration Health Care After Demobilizing From OEF/OIF Deployment. Issue 10 (1st October 2014) - Harris, Alex H. S.; Chen, Cheng; Mohr, Beth A.; Adams, Rachel Sayko; Williams, Thomas V.; Larson, Mary Jo
ABSTRACT: This study described rates and predictors of Army National Guard and Army Reserve members' enrollment in and utilization of Veteran Health Administration (VHA) services in the 365 days following demobilization from an index deployment. We also explored regional and VHA facility variation in serving eligible members in their catchment areas. The sample included 125, 434 Army National Guard and 48, 423 Army Reserve members who demobilized after a deployment ending between FY 2008 and FY 2011. Demographic, geographic, deployment, and Military Health System eligibility were derived from Defense Enrollment Eligibility Reporting System and "Contingency Tracking System" data. The VHA National Patient Care Databases were used to ascertain VHA utilization and status (e.g., enrollee, TRICARE). Logistic regression models were used to evaluate predictors of VHA utilization as an enrollee in the year following demobilization. Of the study members demobilizing during the observation period, 56.9% of Army National Guard members and 45.7% of Army Reserve members utilized VHA as an enrollee within 12 months. Demographic, regional, health coverage, and deployment-related factors were associated with VHA enrollment and utilization, and significant variation by VHA facility was found. These findings can be useful in the design of specific outreach efforts to improve linkage from the Military Health System to the VHA.